Population pattern and phenological behaviours for selected medicinal plants in Nigeria; implications for ex-situ conservation (2013)
Recent developments indicated increasing gene-pool depletion for most medicinal plants in Nigeria despite their pharmaceuticals and therapeutic potentials. Initial socio-economic study involving three countries (Nigeria, Ghana and Republic of Benin) identified ten most frequently used medicinal plants. This list was superimposed on a vegetation map of Nigeria for the production of a distribution map ahead of an eco-geographic survey for population and phenological studies. Sample sites were defined in east-west directions under different vegetation and land use types. Sample sizes of 50m x 50m quadrant were selected across the vegetation and land use types. Altogether 55 samples quadrats were recorded across the zones; Lowland rainforest (20), Derived savanna (16), Sudan savanna (13) and Guinea savannah (6). A total of 196 individuals were recorded across the four ecological zones, rainforest 66 (33.67%) and least in Sudan savanna 13 individuals (6.63%). On land use basis, plantation forest recorded the highest in the lowland rainforest zone and least in sacred groove with similar trend in Derived savanna. In Guinea savanna, farm lands had the highest number of individuals while forest plantation accounted for the highest in Sudan savanna. Flowering duration varied greatly, ranging from (8.42 ±0.83) days to (45.25 ±5.77) days. Fruiting patterns ranged between (14.44± 4.28 to 145.87± 8.76) days. The need for adequate phenological information ahead of ex-situ conservation programme is desirable. Low stocking density observed across the range and land use types is implicated for holistic conservation strategies and sustainability